Analisis Morfologi Koloni dan Pewarnaan Gram Jamur Isolat Singkong (Manihot Esculenta) - Novita Maharani; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Cassava (Manihot esculenta) is a staple food that is widely consumed by the Indonesian population, especially in rural areas. However, during post-harvest handling and storage, cassava is highly susceptible to contamination by microorganisms, particularly fungi. These fungi can cause damage to the food, reduce its nutritional quality, and even produce mycotoxins that are harmful to human health. The increased risk of contamination has become an important concern in efforts to improve the quality and safety of cassava food products. This study aimed to identify the morphology of fungal colonies and the characteristics of fungal cell walls isolated from cassava stored in open environmental conditions for several days. The methods used in this study included isolation using Potato Dextrose Agar (PDA) media, macroscopic observation of fungal colony morphology, including color, edge, elevation, and texture, as well as Gram staining to observe the fungal cell wall properties. The results of this study revealed a diversity of fungal colony morphology, with three dominant types suspected to belong to the genera Aspergillus, Penicillium, and Rhizopus. Gram staining showed that the three isolates were characterized as Gram-negative, indicated by the absorption of safranin as the secondary stain. This study provides an initial overview of the types of fungi that may develop on cassava during storage, and it offers a foundation for further studies on the toxicity and food microbiology applications related to cassava. Morphological identification and Gram staining play an essential role in the initial screening before molecular identification is performed.